'It's a tough drug to kick': a woman's career in broadcasting. (February 2016) - Eikhof, Doris Ruth; York, Charlotte
Research on creative work typically focuses either on precarious work and employment or on creative workers' dedication to their work and profession. The account of UK broadcaster and writer Charlotte presented in this article bridges these two foci. Charlotte talks about finding work in the cultural industry she loves, moulding a portfolio of jobs into a coherent creative career, and being a woman and working mother in broadcasting and media. Her account gives rich insight into how creative workers exercise individual agency in the face of their industries' structural constraints and how they pursue careers both because of and in spite of what the cultural and creative industries offer.